Domestic Violence Legislation and Protection for Survivors: Challenges and Progress in Enforcement - Daniel Ochieng; Sarah Nabirye; James Kalungi (International Journal of Social Welfare and Family Law, 2024)
This research examines the effectiveness of domestic violence legislation in protecting survivors and ensuring access to justice. By analyzing case studies, the study highlights the progress and challenges in enforcement, such as legal gaps, cultural barriers, and resource constraints. Findings suggest that while legislation has improved protections, additional support mechanisms and public awareness are essential to provide survivors with adequate safety and support.